Enhancing the Shopping Experience in E-Commerce: A Path to Improvement – Buy the Best - Sarama Shehmir, Sarama; Nazar, Mobeen; Zaveri, Ayesha Anees; Sami , Naveera; Mashood, Ramsha; Faisal , Nabiha; Waqas, Abdul; Naeem, Rimsha (Bulletin of Social Informatics Theory and Application, 2024)
This research paper presents the development of "Buy by Best," a user-friendly platform designed to save users' time by providing a consolidated shopping experience. The project addressed the inconvenience of visiting multiple websites and logging in to various accounts to shop for different brands. Extensive research was conducted to explore existing shopping websites, user behaviors, and industry trends. The project team analyzed multiple sites, considering brand reputation, product variety, and user experience. Based on the findings, "Buy by Best" was developed to streamline the shopping process. The platform features a centralized login where users can access products from various brands, eliminating the need for multiple website visits and logins. Technologies like the MERN stack and Python libraries like Selenium and Beautiful Soup were used for web development and web scraping of brand products. The platform offers a user-friendly interface with options to browse products by brand, apply filters, and view product details. Users can place orders seamlessly and be redirected to the brand's official website. Future work includes developing a mobile application, enhancing the user interface, expanding the range of brands, and integrating other platforms. In conclusion, "Buy by Best" offers users a convenient and time-saving solution by consolidating products from various brands into a single platform. The project successfully achieves its objective through web scraping, user authentication, and intuitive interfaces.